The determination of chemical elements in food : (Wiley-Interscience, 2007)
This volume, made up of 22 chapters, describes the use of atomic spectroscopy and mass spectrometry in food analysis. Particular emphasis is given to atomic absorption spectrometry, inductively coupled plasma atomic emission spectrometry, and inductively coupled plasma mass spectrometry. Progress in the field is detailed, with discussion of problems that necessitate more development. Specific topics cover fundamental aspects and method development, the quantification of chemical elements in food matrices, legal provisions, the development of instrumental spectrometric techniques, the hyphenation of spectrometric equipment with chromatographic instrumentation, and the adoption of quality schemes with the use of reference materials and proficiency testing schemes. The book is aimed at scientists in food laboratories in the public and private sectors and academia, and members of regulatory bodies that deal with food safety. Contributors are an international group of scientists in chemistry, food quality, public health, and other fields. Both subject and author indexes are provided. Caroli is associated with the Department of Food and Animal Safety at the National Institute of Health in Rome